Beyond Soft Power: A Critical Review of Inequality, Authenticity, and Sustainability in Food Diplomacy - Nazir, Novizar; Putri, Annisyia Zarina; Putri, Aisyah Shakira; Hariry, Amelia (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Food diplomacy has increasingly attracted scholarly attention as a potent form of soft power used to shape national images and influence foreign publics. However, while much of the existing literature celebrates food diplomacy as an effective and benign instrument of cultural exchange, fewer studies critically interrogate its limitations, power dynamics, and long-term implications. This critical literature review evaluates key academic contributions by examining dominant theoretical perspectives, assessing empirical case studies, and identifying significant conceptual gaps. Moving beyond the standard narrative of "winning hearts and minds" , this paper argues that food diplomacy functions as a site of political contestation where authenticity is constructed and regulated for state interests. The review identifies critical tensions, including the commodification of culinary heritage, the marginalization of local producers in favor of elite actors, and the conflict between export-oriented diplomacy and domestic food security. Furthermore, it highlights the lack of robust empirical evidence linking gastrodiplomacy to measurable diplomatic outcomes and questions the superficial use of sustainability narratives. The paper concludes by proposing a future research agenda that integrates political economy, ethics, and rigorous impact evaluation to provide a more holistic understanding of food’s role in international relations. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 10: Reduced InequalitiesSDG 12: Responsible Consumption and Production.SDG 17: Partnerships for the Goals